Pengaruh Konsumsi Rebusan Daun Pandan terhadap Tekanan Darah Wanita Lansia Penderita Hipertensi di Nusalaut Maluku Tengah - Restichia Sasabone; Yenny Aulya; Retno Widowati (Universitas Baiturrahim, 2023)
Hypertension is a condition where a person experiences an increase in blood pressure above normal where the systolic pressure is 140 mmHg and the diastolic pressure is 90 mmHg, so that it can lead to pain, complications and death. As the age of elderly women increases, the risk of developing hypertension becomes greater and will cause problems if not addressed or prevented. Hypertension control can be done by pharmacological and non-pharmacological treatment with the application of herbal plants, that is Pandanus amaryllifolius leaf decoction. This study aims to determine the effect of consumption of pandan leaf decoction on the blood pressure of elderly women with hypertension in the work area of Ameth Public Health Nusalaut Central Maluku. The research design used was a quasi-experimental design with a pre and post test design with a control group. The research sample amounted to 34 respondents consisting of 17 people in the experimental group and 17 people in the control group. The sampling technique used purposive sampling. Data analysis used Wilcoxon test and Man Whitney test. The results of the Wilcoxon test showed that the systolic and diastolic blood pressure of the experimental group had p value < 0.05, while the control group's systolic blood pressure was p value < 0.05 and diastolic blood pressure was > 0.05. diastolic pressure, but not significant to the control group diastolic pressure. The results of the Man Whitney test showed that the systolic blood pressure value was p < 0.05 and the diastolic p value was > 0.05. This shows that there are significant differences in the decrease in systolic blood pressure, but not significant differences in diastolic pressure. Consumption of pandan leaf decoction affects the blood pressure of women with hypertension. Pandanus amaryllifolius leaf decoction can be applied in non-pharmacological treatment as a companion for hypertension treatment in health care institutions